The Influence of School Principal Leadership and Teacher Performance on Academic Achievement of Students of Sentani 3 State High School - Okta Anita Pouw; Dety Mulyanti; Farida Yuliaty (Departement of Mathematics Education, 2024)
As a first step, the researcher conducted an interview with the Principal of SMA Negeri 3 Sentani, stating that student achievement still needed to be improved. This is shown by the graduation results of SMA Negeri 3 Sentani students who were declared 100% successful, but the school exam results still need to be improved. The object of this research was carried out at SMA Negeri 3 Sentani, Jayapura Regency, Papua Province over a period of 3 months. This research aims to analyze the influence of the principal's leadership and teacher performance on the academic achievement results of students at SMA Negeri 3 Sentani, Jayapura Regency, Papua Province. The type of research recommended is ex facto post facto research. Data collection techniques using documentation studies, questionnaires, observations. The population in this study were all teachers at SMA Negeri 3 Sentani, totaling 22 teachers. Research at SMA Negeri 3 Sentani revealed a significant relationship between principal leadership, teacher performance and student academic achievement. The results show that the average score for principal leadership and student academic achievement is 3.91, and teacher performance is 3.64, with a low standard deviation, indicating data consistency. Most respondents appraised the principal's leadership and teacher performance. In conclusion, effective principal leadership and high teacher performance have a positive effect on student academic achievement. This research suggests the importance of synergy between school principals and teachers in creating a conducive learning environment. In addition, principal leadership directly improves academic achievement, with valid data supporting the important role of principals in achieving better educational outcomes. Good teacher performance has also been proven to be closely related to student academic achievement. The combination of principal leadership and optimal teacher performance together makes a significant contribution to student academic achievement, indicating that these two factors must be improved for better educational outcomes at SMA Negeri 3 Sentani.